Pengaruh Sosialisasi Pembelajaran Online terhadap Tingkat Keaktifan Siswa SD di Desa Sumberagung Lamongan: The Effect of Online Learning Socialization on the Activity Level of Elementary School Students in Sumberagung Village, Lamongan - Nafiiyah, Nur; Sari, Ika Purnama (LP2M INSURI Ponorogo, 2021)
Online learning is the newest way of learning, where students can access the material directly even in far places. Online learning is a way to deliver material without having to meet with students. The purpose of this activity is to find a relationship between online learning and the activeness of elementary school students in Sumberagung Mantup Lamongan. The data used in this study, namely: data on the results of student activity in accessing online learning, ranging from participation in accessing e-learning and reading material, participating in discussions in online learning. Student data used as many as 133 students, and the variables of this study, namely the number of values involved in the discussion, the total value of reading material. The results of this study indicate that there is no correlation between students' interest in reading online learning and discussion activeness at online learning, with a correlation value of -0.024. Pembelajaran secara online merupakan cara pembelajaran terbaru, di mana peserta didik dapat mengakses materi secara langsung walaupun di tempat jauh. Pembelajaran online merupakan cara menyampaikan materi tanpa harus bertatap muka dengan peserta didik. Tujuan dari kegiatan ini, yaitu mencari hubungan antara pembelajaran online dengan keaktifan siswa SD di Sumberagung Mantup Lamongan. Data yang digunakan dalam penelitian ini, yaitu: data hasil keaktifan siswa dalam mengakses pembelajaran online, mulai dari keikutsertaan dalam mengakses e-learning dan membaca materi, ikut serta dalam berdiskusi dalam pembelajaran online. Data siswa yang digunakan sebanyak 133 siswa, dan variabel dari penelitian ini, yaitu jumlah nilai ikut berdiskusi, jumlah nilai membaca materi. Hasil penelitian ini menunjukkan bahwa tidak adanya korelasi antara minat membaca siswa dalam pembelajaran online terhadap keaktifan berdiskusi pada pembelajaran online, dengan nilai korelasi -0,024.